1
$\begingroup$

How can I solve problems like this:

Let ${c_1,c_2,c_3,c_4,c_5,c_6}$ be a random sequence where $c_i\in (0,1,2,3,4,5,6,7,8,9)$ What is probability that $c_1+c_2+c_3=c_4+c_5+c_6$,

$c_1$ to $c_6$ is not a number there can be all zeroes and combination like $1,1,1$ etc. is possible.

I have a problem with getting how many is combinations there are. I saw that for a specific number like $c_1+c_2+c_3=12$, it is possible to use a generating function, but I don't know how to use it when we have statement like in this problem.

$\endgroup$
  • $\begingroup$ Are these supposed to be the digits of 6-digit natural number? Because if so then the first digit has to be non-zero. $\endgroup$ – Keen-ameteur Nov 18 '18 at 14:55
  • 1
    $\begingroup$ Are the numbers chosen with or without replacement? $\endgroup$ – Ross Millikan Nov 18 '18 at 14:57
  • $\begingroup$ Please edit your question to show what you have attempted and explain where you are stuck so that you receive responses that address the specific difficulties you are encountering. $\endgroup$ – N. F. Taussig Nov 18 '18 at 15:25
2
$\begingroup$

It seems that you know how to compute $$p_k:=P\bigl[c_1+c_2+c_3=k\bigr]\qquad(0\leq k\leq27)\ .$$ The final result $p$ is then simply given by $$p=\sum_{k=0}^{27}p_k^2\ .$$ By the way: The generating function for the number of choices of $c_1$, $c_2$, $c_3$ summing to a given $k$ is $$\left(\sum_{i=0}^9 x^i\right)^3=(1-x^{10})^3(1-x)^{-3}=(1-3x^{10}+3x^{20}-x^{30}\bigr)\sum_{j=0}^\infty{2+j\choose j}x^j\ .$$

$\endgroup$
0
$\begingroup$

You are looking for $$N_{\,b} (s,r,m) = \text{No}\text{. of solutions to}\;\left\{ \begin{gathered} 0 \leqslant \text{integer }x_{\,j} \leqslant r \hfill \\ x_{\,1} + x_{\,2} + \cdots + x_{\,m} = s \hfill \\ \end{gathered} \right.$$

which is given by $$ N_b (s,r,m)\quad \left| {\;0 \leqslant \text{integers }s,m,r} \right.\quad = \sum\limits_{\left( {0\, \leqslant } \right)\,\,k\,\,\left( { \leqslant \,\frac{s}{r+1}\, \leqslant \,m} \right)} {\left( { - 1} \right)^k \binom{m}{k} \binom { s + m - 1 - k\left( {r + 1} \right) } { s - k\left( {r + 1} \right)}\ } $$ as widely explained in this related post.

Of course in this case it is $m=3$ , $r=9$ amd $0 \le s \le 27$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.